If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (30x) = (31x + -2) Reorder the terms: (30x) = (-2 + 31x) Remove parenthesis around (-2 + 31x) (30x) = -2 + 31x Solving (30x) = -2 + 31x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31x' to each side of the equation. (30x) + -31x = -2 + 31x + -31x Combine like terms: (30x) + -31x = -1x -1x = -2 + 31x + -31x Combine like terms: 31x + -31x = 0 -1x = -2 + 0 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| t-37+t=t+30 | | 4h-70=12h+2 | | -7.678+(-29)= | | 8.3x-18=9x | | 14y-13y=13 | | (5x-7)+(3x+8)= | | (u-7)*10=70 | | -3/4a | | 45x^4-100x+55=0 | | g-1= | | g(x)=5x+65 | | 2y^2-4y-20=0 | | 2x-8+5x-32=180 | | 3a+6+4= | | 2x-6+90+48=180 | | (q+7)*5=45 | | 90+y+2+3y=180 | | g(x)=-4x+15 | | 50-4x=-61-6x | | 7m-6m=4 | | 4+[7-m]=5 | | (5*5)+(b*b)=(16*16) | | 25x-27x=7-9 | | 5k-4k=6 | | 3x-5=7k+7 | | 2x+2=4x+2+x | | g(x)=-4x+30 | | 11+2lnx=4 | | 3(c-9)=3 | | 2c^4-6c^3=12c^2+36c | | 3x+3x-7=65 | | K+20=7 |